Korelasi Motivasi Belajar terhadap Kemandirian Belajar PAI Peserta Didik di SMA Negeri 17 Bandar Lampung - Jaya Gusnanda; Imam Syafe'i; Rudy Irawan (MAN 4 Kota Pekanbaru, 2026)
This study aims to examine the effect of learning motivation on students' learning independence in Islamic Religious Education (PAI) subjects in grade X of SMA Negeri 17 Bandar Lampung. Using a quantitative approach with a correlational design, this study involved 54 students from a population of 120 people selected using a simple random sampling method. Data were collected through a Likert scale questionnaire that had met validity and reliability tests. Data analysis included normality tests, linearity tests, simple linear regression tests, t-tests, and coefficients of determination. The results of the study proved that learning motivation has a positive and significant influence on learning independence (significance 0.021 < 0.05). The coefficient of determination value of 0.098 indicates that learning motivation only contributes 9.8% to learning independence, while 90.2% is determined by other factors. Thus, increasing learning motivation has been proven to be able to improve the development of student independence in PAI learning.